Clinical Outcomes Associated With Adjunctive Electroacupuncture During Standard Exercise Rehabilitation in Individuals With Spinal Cord Injury: A Retrospective Propensity Score-Matched Cohort Study - Ying Zhang; Xianhong Zuo; Liwen Guo; Guoqing Zheng; Xinming Yang (Acupuncture & Electro-Therapeutics Research: International Journal of Integrated Medicine, 2026)
Objective This article aims to examine whether adjunctive electroacupuncture was associated with more favorable rehabilitation outcomes among individuals with spinal cord injury (SCI) receiving standard exercise rehabilitation. Methods In this single-center retrospective cohort study, 174 patients with SCI treated between January 2020 and December 2025 were screened. After 1:1 propensity score matching for age, sex, body mass index, injury level, broad etiology (traumatic vs non-traumatic), and American Spinal Injury Association Impairment Scale grade, 86 patients were analyzed: 43 received exercise rehabilitation alone, and 43 received adjunctive electroacupuncture. Both groups completed an 8-week rehabilitation course. Outcomes included residual urine volume, daily urination frequency, Modified Ashworth Scale (MAS), Composite Spasticity Index (CSI), Spinal Cord Independence Measure III (SCIM-III), International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) motor and sensory scores, oxidative-stress markers, and documented adverse events. Results The covariates included in the matching model were balanced after matching. Within-group comparisons showed improvement in bladder parameters, spasticity, independence, neurological scores, and oxidative-stress markers. At 8 weeks, the adjunctive electroacupuncture group had lower residual urine volume, urination frequency, MAS and CSI scores, and malondialdehyde, together with higher SCIM-III, ISNCSCI motor and sensory scores, glutathione peroxidase, and superoxide dismutase than the exercise-only group (all P < 0.05). Documented adverse-event proportions were 13.95% and 11.63% ( P = 0.747); however, the complete-case retrospective design was not sufficient to establish comparative safety. Conclusion Among complete cases, adjunctive electroacupuncture was associated with more favorable post-treatment functional, neurological, and oxidative-stress values during an 8-week rehabilitation course. These findings should be interpreted cautiously because the exact interval from injury or disease onset to rehabilitation, detailed non-traumatic etiologies, and several treatment-related confounders were unavailable.